Pelatihan Kewirausahaan bagi Wirausaha Pemuda Karang Taruna dan PKK Desa Kaladawa, Kecamatan Talang, Kabupaten Tegal - M. Masrukhan (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Entrepreneurship training is a key strategy for empowering village economies, especially among youth from Karang Taruna and PKK members. In Kaladawa Village, local potential such as agriculture and handicrafts has not been fully utilized due to limited entrepreneurial knowledge and exposure. This program aims to enhance participants' entrepreneurial competencies through practical-based training methods, including interactive lectures, group discussions, and business simulations. A participatory approach was implemented to help participants identify local potentials, develop business ideas, and formulate digital-based marketing strategies. The results of the training indicate a significant improvement in participants’ understanding of entrepreneurship, as reflected in the emergence of innovative business plans focused on local and digital products. Pre- and post-training evaluations showed increased motivation, creativity, and readiness among participants to initiate independent ventures. The training also fostered a sustainable entrepreneurial spirit by covering essential topics such as financial management, digital transformation, and business networking. Participants acknowledged that direct experiences and intensive mentoring during the sessions played a crucial role in building their confidence and competitiveness. However, for long-term success, continuous mentoring and institutional support are required, along with strategic collaboration between stakeholders such as village governments, local MSMEs, and higher education institutions. Thus, this program not only contributes to improving technical and entrepreneurial skills but also plays a pivotal role in developing a self-reliant and sustainable rural entrepreneurial ecosystem. The integration of similar training into broader community empowerment programs is recommended to ensure lasting impact, inclusive access, resilience, innovation, adaptability, creativity, empowerment, collaboration, leadership, and meaningful local economic development.